GREEN BANKING EVOLUTION: MAPPING THE STATE-OF-THE-ART OF LITERATURE - Rahman, Liyana Ab; Shamsudin, Siti Marlia; Mohamad, Maslinawati; Nahar, Hairul Suhaimi (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
The urgency to address environmental degradation and climate change has placed significant pressure on financial institutions to adopt sustainable practices. As a primary facilitator of economic activity, the banking sector can mitigate its environmental impact through green banking initiatives. However, despite the increasing importance of sustainable finance, research on the trends, key contributors, and development of green banking still needs to be completed and expanded. This study addresses such issues by investigating the evolution of the green banking literature over an extended period from 1996 to 2021 to map the field’s intellectual structure. Adopting an established bibliometric approach, this study uses a bibliometric analysis to identify research trends, publication patterns, key authors, and gaps in green banking. A dataset of 115 documents was sourced from the Scopus database, covering areas such as economics, finance, and environmental science. Using tools such as Harzing’s Publish or Perish and VOSviewer, citation and co-authorship networks were examined along with keyword co-occurrences. The results show that green banking research has grown exponentially, with most contributions from Asia, particularly Malaysia. The analysis identified nine research clusters, highlighting key themes such as sustainable development and corporate social responsibility. Furthermore, the findings reveal limited collaboration between researchers and suggest that more cross-country studies are needed to enhance global understanding of green banking practices. Overall, this study provides the first comprehensive bibliometric review of green banking, offering insights for researchers and policymakers into this growing field’s current state and future directions. JEL Classification Codes: G21, Q56, Q58.